2015
DOI: 10.1182/blood.v126.23.1497.1497
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Discordant Indolent Lymphomas: A Subset of Indolent NHLs with a Less Favorable Prognosis and Propensity to Transform

Abstract: INTRODUCTION: The typical presentation of patients with low grade lymphoma consists of disseminated lymphadenopathy, absence of constitutional symptoms, normal LDH, low Ki-67 and PET scan with low SUVs (i.e. <14). We have identified a subset of atypical cases who present with one or more clinically aggressive features. We have named these cases clinically discordant indolent histologies (CDIH). The goal of this study is to identify these cases with CDIH in order to determine if their prognosis and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Unfortunately, a subset of patients performs poorly despite treatment . These patients have been described as “clinically discordant indolent lymphomas.” At diagnosis, prognosis may be predicted using standard indices . These indices do not reliably predict early therapeutic failure, defined as relapse within 2 years of treatment with immunochemotherapy (IC) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, a subset of patients performs poorly despite treatment . These patients have been described as “clinically discordant indolent lymphomas.” At diagnosis, prognosis may be predicted using standard indices . These indices do not reliably predict early therapeutic failure, defined as relapse within 2 years of treatment with immunochemotherapy (IC) .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested additional factors may predict inferior outcome. These include vitamin D insufficiency, high tumor proliferative rate, and high metabolic tumor volume (MTV) by positron emission tomography‐computed tomography (PET/CT) . The number of extranodal (EN) sites involved with FL has traditionally been defined as tumor involvement of non‐nodal sites determined by imaging; or, bone marrow involvement detected by bone marrow biopsy (BMB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation